Nghiên cứu sản xuất axit axetic - Hồ, Quý Đạo (2011)
Tác giả: Hồ Quý Đạo, TS; Trần Công Khanh, PTS; Nguyễn Minh Hiền. TS; Nguyễn Thị Dư, PTS; Đỗ văn Chín, PTS; Lê Thanh Cẩm, KS -- Từ khóa: Axit axetic; Sản xuất thử; Xúc tác; Thiết bị; Dehydro hóa; Oxy hóa; Hiệu suất